The level of cross-disciplinarity in cross-disciplinary accounting research: analysis and suggestions for improvement - Dellaportas, Steven; Xu, Lina; Yang, Zhiqiang (Elsevier, 2020)
This study examines the extent of cross-disciplinary accounting research using a self-constructed definitional framework developed from a review of diverse literatures to better understand its meaning and underlying dimensions. The two identifiable dimensions, integration (blending of concepts) and interaction (researcher collaboration), sit along a continuum of relationships creating the potential for new knowledge through cross-disciplinary research. Data analysis using the publication descriptors from three highly regarded cross-disciplinary accounting research journals (AAAJ, AOS, CPA) suggest that cross-disciplinary accounting research is underpinned by conceptual 'integration' but less emphasis is placed on the 'interaction' between researchers of diverse disciplines. The findings also indicate that cross-disciplinarity is associated with higher citations. Interestingly, we found that the interaction dimension has a growing effect, over time, on article citations.